Transforming Organization into Social Business - Ončo, Martin; Pavlíček, Antonín, 1977-; Švík, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2013)
Social networks like Facebook, Twitter or LinkedIn offer the opportunity to communicate and collaborate with friends and family in our personal life through the social technology without seeing each other on daily bases. This different approach is already common to be used for the majority of people and brings new benefits to now-a-day global environment. The same users of these external social networks are working in companies with various internal collaboration and communication tools. This fact has become stimulus for the theory of using social network technologies inside of the organization called Social Business. Social Business brings multiple new benefits for the organization, which were not possible to be gain through the previous approaches of communication and collaboration. In the present work we study the process of transforming organization into Social Business.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses